Extensive Reduction in Back Electron Transfer in Twisted Intramolecular Charge‐Transfer (TICT) Coumarin‐Dye‐Sensitized TiO2 Nanoparticles/Film: A Femtosecond Transient Absorption Study. Issue 12 (24th February 2014) - Debnath, Tushar; Maity, Partha; Lobo, Hyacintha; Singh, Balvant; Shankarling, Ganapati S.; Ghosh, Hirendra N.
Abstract We report the synthesis, characterization, and optical and electrochemical properties of two structurally similar coumarin dyes (C1 and C2). These dyes have been deployed as sensitizers in TiO2 nanoparticles and thin films, and the effect of molecular structure on interfacial electron‐transfer dynamics has been studied. Steady‐state optical absorption, emission, and time‐resolved emission studies on both C1 and C2, varying the polarity of the solvent and the solution pH, suggest that both photoexcited dyes exist in a locally excited (LE) state in solvents of low polarity. In highly polar solvents, however, C1 exists in an intramolecular charge‐transfer (ICT) state, whereas C2 exists in both ICT and twisted intramolecular charge‐transfer (TICT) states, their populations depending on the degree of polarity of the solvent and the pH of the solution. We have employed femtosecond transient absorption spectroscopy to monitor the charge‐transfer dynamics in C1‐ and C2‐sensitized TiO2 nanoparticles and thin films. Electron injection has been confirmed by direct detection of electrons in the conduction band of TiO2 nanoparticles and of radical cations of the dyes in the visible and near‐IR regions of the transient absorption spectra. Electron injection in both the C1/TiO2 and C2/TiO2 systems has been found to be pulse‐width limited (<100 fs); however, back‐electron‐transfer (BET) dynamics has been found to be slower in the C2/TiO2 system than in the C1/TiO2 system. The involvement of TICT states in C2 is solely responsible for the higher electron injection yield as well as the slower BET process compared to those in the C1/TiO2 system. Further pH‐dependent experiments on C1‐ and C2‐sensitized TiO2 thin films have corroborated the participation of the TICT state in the slower BET process in the C2/TiO2 system.